APPLICATION OF COOPERATIVE LEARNING MODEL JIGSAW IN INCREASING STUDENTS LEARNING ACHIEVEMENT OF SOCIAL SCIENCE SUBJECT - Elvadwi Sholissafitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2022)
This Classroom Action Research (CAR) aims to determine the improvement in social studies learning achievement of the fifth grade students of SDN 15 Cakranegara in the 2018-2019 school year, totaling 23 people, consisting of 14 boys and 9 girls. The research method used is: Cooperative Learning Model Jigsaw technique, with data collection techniques in the form of observation and evaluation tests, then analyzed qualitatively by comparing the success rates between cycles. The results of this study indicate an increase in the number of students who complete learning or get a score of 63, namely 15 students in the first cycle to 18 students in the second cycle. An increase also occurred in the average value of the evaluation test given after the learning process was over, namely: 70.21 in the first cycle, to 72.39 in the second cycle. While the percentage of student learning completeness in each cycle, which is 66.67% in the first cycle, increased to 80.00% in the second cycle. In addition, the application of this method can also increase the activities of teachers and students which increase from cycle I to cycle II. This is evidenced by the percentage of teacher activity which increased from 69.10% in the first cycle with a fairly good category, to 87.85% in the second cycle with a good category. The increased student activity was marked by 68.74% in the first cycle with a fairly good category, to 82.71% in the second cycle with a good category. The Jigsaw Cooperative Learning Model has been able to improve the social studies learning achievement of fifth graders at SDN 15 Cakranegara for the 2018-2019 school year.